2017
DOI: 10.1007/s00441-017-2576-1
|View full text |Cite
|
Sign up to set email alerts
|

MCL-1 is modulated in Crohn’s disease fibrosis by miR-29b via IL-6 and IL-8

Abstract: The miR-29 family is involved in fibrosis in multiple organs, including the intestine where miR-29b facilitates TGF-β-mediated up-regulation of collagen in mucosal fibroblasts from Crohn’s disease (CD) patients. Myeloid cell leukemia-1 (MCL-1), a member of the B-cell CLL/Lymphoma 2 (BCL-2) apoptosis family, is involved in liver fibrosis and is targeted by miR-29b via its 3’-UTR in cultured cell lines. We investigate the role of MCL-1 and miR-29b in primary intestinal fibroblasts and tissue from stricturing CD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 47 publications
1
23
0
Order By: Relevance
“…Among the selected methylation sites, C7orf72 18 and HLA-DRB1 19 had been confirmed to be related to CD by GWAS. As mentioned previously, MUC1 35 38 and YPEL5 39 were genes involved in the process of apoptosis, which proved that CD penetrating intestinal mucosal lesions were related to apoptosis. Methylation abnormalities in MUC1 also suggested that CD penetrating intestinal mucosal lesions were associated with ECM abnormalities.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Among the selected methylation sites, C7orf72 18 and HLA-DRB1 19 had been confirmed to be related to CD by GWAS. As mentioned previously, MUC1 35 38 and YPEL5 39 were genes involved in the process of apoptosis, which proved that CD penetrating intestinal mucosal lesions were related to apoptosis. Methylation abnormalities in MUC1 also suggested that CD penetrating intestinal mucosal lesions were associated with ECM abnormalities.…”
Section: Discussionsupporting
confidence: 67%
“…Interestingly, the MUC1 expression in CD was reduced in earlier studies 33 , 34 . In addition, studies 35 38 had confirmed that MUC1 was confirmed to be involved in multiple apoptosis signaling pathways.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The up-regulated IL21R also suggested B cell maturation, since the B cell differentiation required direct IL21R signals (King et al, 2010 ). In addition, the down-regulated MCL1 mediated by miR-429b suggested that there was a weakening in MCL1's protection from epithelial apoptosis (Lv et al, 2014 ; Nijhuis et al, 2017 ). This was in accordance with the finding that SBM diet increased turnover of intestinal epithelial cells (Chikwati et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mott et al [19] reported that miR-29b is an important endogenous regulator, which plays a role in endothelial cell apoptosis by inhibiting the anti-apoptotic gene, myeloid cell leukemia-1. Anke and his team also showed that miR-29b mediates the deposition of collagen and fibrosis via IL-6 and tumor growth factor-β [20]. miR-29b has also been suggested to suppress the proliferation and migration of vascular smooth muscle cells, possibly through inhibition of myeloid cell leukemia-1 and matrix metalloproteinase-2, indicating that miR-29b may serve as a valuable therapeutic tool to treat CVD, such as atherosclerosis [21].…”
Section: Discussionmentioning
confidence: 99%